Analysis of e-Service Quality, e-Trust, Promotion, e-Customer Satisfaction, and e-Customer Loyalty of Flip Application Customers in the Special Region of Yogyakarta - Prasetyo, Edo Budi; Oetomo, Hadi; Liestyana, Yuli; Sukarno, Agus; Sutanto, Hery (Journal of International Conference Proceedings, 2023)
This research aims to find the effect of service quality, e-trust, and promotion on customer loyalty mediated by e-customer satisfaction with the Flip application in the Special Region of Yogyakarta. This research uses purposive sampling techniques. The number of samples used in this research was 105 respondents. The data analysis tool used in this research is Partial Least Square (PLS). The results in this study are (1) e-service quality positively affects customer satisfaction, (2) e-service quality positively affects customer loyalty, (3) e-trust positively affects customer satisfaction, (4) e-trust positively affects customer loyalty, (5) promotion positively affects customer satisfaction (6) e-customer satisfaction positively affects customer loyalty (7) e-service quality positively affects customer loyalty through e-customer satisfaction (8) e-trust positively affects customer loyalty through e-customer satisfaction (9) promotion positively affects customer loyalty through e-customer satisfaction. The research team suggests that Flip companies pay more attention to e-service quality through several indicators, such as improving the application to avoid frequent errors, compensating users if an application system error occurs during transactions, and providing better service assistance contacts.